Union of South Africa. Debates of the House of Assembly Third Session, Fifth Parliament 1926 - South Africa Parliament (Cape Town Government Printer, 1926)
Debates of the House of Assembly / Union of South Africa. South Africa Politics and government.
Debates of the House of Assembly Union of South Africa. 4th Session, 4th Parliament, vol. 1 (25 Jan.-10 Apr. 1924)-4th Session, 12th Parliament, v. 108 (1 May-26 May 1961)
Keywords: 1926; January to June; vol 7; Third Session - Fifth Parliament; March to June; Union of South Africa; House of Assembly; JC044668; Debates